PENGARUH KONSUMSI ENERGI DAN PAJAK DENGAN MEDIASI PERTUMBUHAN EKONOMI TERHADAP POLUSI DI 9 NEGARA ASEAN - Kenedi Kenedi (Jurnal Bina Bangsa Ekonomika, 2022)
Global warming and climate change over the past ten years caused by greenhouse gas emissions are serious problems faced by countries in both developed and developing countries, not least in countries in ASEAN. The relationship of energy consumption, the application of tax burdens, economic growth and its effect on pollution levels are important to be investigated further. The aim of the study was to analyze the effect of energy consumption and taxes by mediating economic growth on pollution in nine ASEAN countries (Indonesia, Cambodia, Laos, Myanmar, Malaysia, philippines, Singapore, Thailand and Vietnam). This study used time series data from 2004 - 2020 with analytical methods using the PLS-SEM approach and SmartPLS version 3.0 as data analysis tools. The results of the study showed that energy consumption has a positive effect on economic growth and pollution, taxes have a positive effect on economic growth and negatively affect pollution and economic growth has a positive effect on pollution, in addition, economic growth can mediate the relationship between energy consumption and pollution and the relationship between taxes and pollution